KOMODITAS UNGGULAN TANAMAN PANGAN DI PULAU JAWA - Agus dwi Nugroho (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2010)
Existence of a region will depend heavily on the accuracy of decision-makers in determining the direction of regional development, especially relating to the development sector basis. Agricultural sector, particularly food crops is one of the key sectors in the island of Java. The purpose of this study was to determine pre-eminent food commodities each province on the Java. The method used in this research is descriptive analysis. Type of data used in Indonesiathan in 2006-2008. The analysis used in this study is the Location Quotient (LQ) and Dynamic Location Quotient (DLQ). Pre eminent crops in Bnaten province that have two of rice and peanuts. Pre eminent crops in the West Java rice and weet potatoes. DKI has one pre-eminent crops that is rice. Central java has four pre eminent crops corn, green beans, peanuts and soybeans. Pre eminent crops in the DIY is peanuts and cassava. East java provincehas four pre eminent, crops corn, green neams, peanuts and soybeans.